2020
DOI: 10.18805/ijar.b-4168
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological Diagnosis of Transmissible Venereal Tumour with Hepatozoon canis and Babesia canis Infection in a Chippiparai Dog

Abstract: Background: The concurrent infection of tick borne haemoprotozoan diseases like B.canis, E.canis and H.canis were commonly recorded in breed dogs. There is paucity in recording the combined haemoprotozoan infection with neoplasms in the native breeds of Tamil Nadu. The current investigation was documented to study the clinico-pathological changes, diagnosis and treatment of the concomitant infection of Hepatozoon canis and Babesia canis along with transmissible venereal tumor in a native dog.Methods: This Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The cytological study from the genital mass confirmed the presence of transmissible venereal tumour and the blood smear of the same dogs also had the gamonts in the neutrophils. In one Babesia canis co-infected anaemic dog and a dog with continuous bleeding in genital mass had severe reduction in haematological parameters were observed viz., reduction in haemoglobin, packed cell volume and red blood cells [3]. The blood smears of that case were diagnosed as concomitant infection of B. canis and H. canis (Figure 1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The cytological study from the genital mass confirmed the presence of transmissible venereal tumour and the blood smear of the same dogs also had the gamonts in the neutrophils. In one Babesia canis co-infected anaemic dog and a dog with continuous bleeding in genital mass had severe reduction in haematological parameters were observed viz., reduction in haemoglobin, packed cell volume and red blood cells [3]. The blood smears of that case were diagnosed as concomitant infection of B. canis and H. canis (Figure 1).…”
Section: Resultsmentioning
confidence: 92%
“…In most of these cases, neutrophilic leucocytosis is recorded due to the concurrent infections [13]. To the best of author's knowledge, the morphological alterations of H. canis gamonts and the nucleus (Figure 3 and spleen [3]. In the solitary cases, only in one case there was mild elevation of ALT and ALP might be due to more severity in concentration of parasites and its multiplication [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation